Reintegrating Religion and Science: Ziauddin Sardar's Epistemological Critique of Modern Knowledge - risma sulistia aini; Eva Dewi (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study analyzes Ziauddin Sardar’s concept of integrating religion and science and its relevance for contemporary knowledge and civilization. Rapid scientific and technological development shaped by secular paradigms has generated ethical, ecological, and civilizational crises. At the same time, Muslim societies continue to face epistemological dependence and fragmentation between religious and scientific knowledge. These conditions underscore the need for an integrative framework that reconnects science with moral and spiritual values. This research employs a qualitative library-based method, examining Sardar’s key works alongside recent scholarly literature on Islamic epistemology and science–religion relations. Data are analyzed through qualitative content analysis to identify epistemological assumptions, normative principles, and thematic patterns. The findings show that, first, Sardar views integration as an epistemological reconstruction grounded in tawḥīd, rejecting the assumed neutrality of modern science. Second, his paradigm of Islamic science is value-based, human-centered, rooted in Islamic intellectual tradition, epistemically plural, and future-oriented through futures studies. Third, this integration constitutes a civilizational response to Western epistemological hegemony, moral disconnection in science, and global challenges, including climate change and artificial intelligence. This study contributes to Islamic epistemology and science–religion studies by framing integration as a paradigmatic and civilizational project, and it recommends further empirical research on the implementation of integrative science frameworks in education, policy, and technology.